Regional wage variations in Britain 1850-1914 - Hunt, E. H. (Oxford : Clarendon Press, 1973)
Dr. Hunt begins with a long discussion of money wages for males in thirteen regions of Britain-Ireland being excluded from the analysis. This is the starting-point of his argument. His main findings, reduced to their essentials, are that there were two high wage areas in 1850, these being, first, London and, second, the northern industrial and mining counties including parts of the West Midlands down to Birmingham. By 1914 the position was similar except that South Wales and Central Scotland now came into the high wage bracket; and that within most regions in general, occupational differentials tended to have diminished compared with 1850. In the remaining eight chapters of the volume Dr. Hunt then considers in turn the various economic and social factors which confirmed, eroded or compensated these regional and occupational wage differences. He begins with the cost of living, then goes through the evidence on family earnings, the demand for labour, productivity, population and fertility, internal migration of labour, Irish and other immigration and finally trade unions. In each chapter he provides full documentation and where he thinks necessary a discussion of the usefulness and accuracy of the data used.
Revision of the author's thesis, London.
Includes index.
Includes bibliographical references: p. [367]-371.
rpm 05/04/2018
Loans
Keywords: Wages; Working class; Cost and standard of living